Perstude Lahap: An Alternative Of Violin Effective Learning (Jurnal Seni Musik, 2020)
This article is to describe a research result of violin lesson conduct in Music Art Study Program, Faculty of Language and Arts, UKSW, Salatiga. The research problems are 1) obstructions in learning violin instrument, and 2) finding the right method for the violin learners. It is a Research and Development study aiming to find the effectiveness of the violin learning method named â€œPerstude Lahapâ€. The name stands for Persiapan (preparation or warming up), Etude (practicing), Lagu (song or repertoar), and Menghapal (memorizing). The research shows that it is able to make lesson successful under the requirements that the learners are fast learners or have good intelligence, strongly motivated, persistent, and incorporating right playing method. Perstude Lahap method is one of the effective alternatives for learners as it provides well-structured practice and stimulates learners to optimally develop both their cognitive and motoric skill.